Musical form in the age of Beethoven: Selected writings on theory and method - Marx, Adolf Bernhard 1795-1866; Burnham, Scott (Cambridge University Press, 1998)
A. B. Marx was one of the most important German music theorists of his time. This volume offers a generous selection of the most salient of his writings, the majority presented in English for the first time. It features the oft-cited but little understood material on sonata form, his progressive program for compositional pedagogy and his detailed critical analysis of Beethoven's Eroica Symphony. These writings thus deal with issues that fall directly among the concerns of mainstream theory and analysis in the past two centuries.Show More Show Less